SOCIAL MEDIA DAN MINAT BELI GEN Z (STUDI KASUS INSTAGRAM STARBUCKS INDONESIA) - Natasya Sugianto; Andreas Kiky (Modus, 2023)
Starbucks is a company in the coffee café retail industry that conducts social media marketing via Instagram to market its products and services. In Indonesia, Generation Z users dominate Instagram social media. 4C which consists of context, communication, collaboration, and connection was used to increase consumer buying interest. This study aims to determine the effect of 4C in social media marketing on buying interest partially and simultaneously. This study is quantitative research that uses survey methods. Primary data collection was from the distribution of online questionnaires using Google Forms. Secondary data was collected from previous research, books, survey results, and information from official websites owned by private or government institutions. Population research was from Instagram @starbucksindonesia followers who were classified as Generation Z with a sample of 100 respondents. Samples were collected using a nonprobability technique with a purposive sampling method. The data processing and analysis technique used in this study is multiple linear regression. The study results show a positive effect between context, communication, collaboration, and connection toward buying interest simultaneously and partially. Based on the research results, it would be better if retailers from the MSME to the international scale maximized all 4C variables in social media marketing to increase and maintain consumer buying interest. Messages, information, concepts, and content design preparation must start a month before. So that in the following month, the content schedule that is ready to be posted is available. There must be regular evaluations to check whether the content has achieved its goals. Keywords: buying interest, Instagram, marketing management, social media, social media marketing. Starbucks merupakan perusahaan di industri retail café kopi yang melakukan social media marketing melalui Instagram untuk memasarkan produk dan layanannya. Di Indonesia, Instagram didominasi oleh pengguna yang merupakan generasi Z. 4C yang meliputi context, communication, collaboration, dan connection digunakan dalam membuat konten social media marketing untuk meningkatkan minat beli konsumen. Penelitian ini bertujuan untuk mengetahui pengaruh 4C dalam social media marketing terhadap minat beli secara parsial dan simultan. Penelitian ini berbasis kuantitatif menggunakan metode survei. Pengumpulan data primer dilakukan melalui penyebaran kuesioner secara online menggunakan google form. Data sekunder diperoleh dari penelitian sebelumnya, buku, hasil survei, serta informasi dari website resmi lembaga swasta atau pemerintah. Populasi penelitian diambil dari followers Instagram @starbucksindonesia yang tergolong generasi Z dengan sampel 100 responden. Sampel dikumpulkan menggunakan teknik nonprobability dengan metode purposive sampling. Teknik pengolahan dan analisis data menggunakan regresi linear berganda. Hasil penelitian menunjukkan context, communication, collaboration, dan connection berpengaruh positif terhadap minat beli secara simultan maupun parsial. Berdasarkan hasil penelitian, akan lebih baik jika peretail dari skala UMKM hingga internasional memaksimalkan seluruh variabel 4C dalam social media marketing agar dapat meningkatkan dan mempertahankan minat beli konsumen. Pesan, informasi, konsep, dan desain konten perlu dipersiapkan satu bulan sebelumnya, sehingga jadwal konten yang siap untuk diposting bulan berikutnya sudah tersedia. Evaluasi juga harus rutin dilakukan untuk memeriksa apakah konten yang dibuat telah mencapai tujuan. Kata Kunci: Instagram, manajemen pemasaran, media sosial, minat beli, social media marketing.